1982
DOI: 10.1203/00006450-198205000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hyperphenylalaninemia on Fetal Development: a New Animal Model of Maternal Phenylketonuria

Abstract: SummaryA new model has been developed for the study of maternal phenylketonuria. Beginning on the 12th day of gestation the diet of pregnant rats was supplemented with 0.5% a-methylphenylalanine and 3% phenylalanine. This resulted in an 83% reduction of hepatic phenylalanine hydroxylase activity. The maternal plasma phenylalanine ;vas elevated 10-20-fold for two-thirds of the day, but the degree and persistence of the fetal hyperphenylalaninemia may have been even greater. The brain phenylalanine concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…If appli cable to human maternal PKU, this hypoth esis would provide a reasonable explanation for the fetal brain effect but would leave still unanswered questions such as why the heart is not always defective and why certain other organs are not affected. nylalaninemia have been approximately 10-20% below controls [13,20]. This reduction is an order of magnitude similar to the re duced birth weight noted in maternal PKU offspring.…”
Section: Pathogenesis Of the Fetal Damagesupporting
confidence: 58%
“…If appli cable to human maternal PKU, this hypoth esis would provide a reasonable explanation for the fetal brain effect but would leave still unanswered questions such as why the heart is not always defective and why certain other organs are not affected. nylalaninemia have been approximately 10-20% below controls [13,20]. This reduction is an order of magnitude similar to the re duced birth weight noted in maternal PKU offspring.…”
Section: Pathogenesis Of the Fetal Damagesupporting
confidence: 58%
“…In support of this hypothesis, the Panel noted that administration of a dose of L-phenylalanine (1800 mg/kg bw/day) that was equimolar to 4000 mg aspartame/kg bw/day led to a similar decrease in maternal and pup body weight as observed in a concurrent aspartame group (E49, 1973). Furthermore, supplementation of the diet with L-phenylalanine (5-7 %) (Kerr and Waisman, 1967) or the combination of 3 % Lphenylalanine and 0.5 % α-methylphenylalanine (Brass et al, 1982) has been shown to result in severe nutritional imbalance in rats (Kerr and Waisman, 1967) and to lead to a reduction in pup body weight at birth (Brass et al, 1982). In addition, milk production in mothers exposed to excessive Lphenylalanine intake has been reported to be decreased, which could further contribute to malnutrition of the pups during weaning and result in pup mortality (Boggs and Waisman, 1962;Kerr and Waisman, 1967).…”
Section: Discussion Of Aspartame Toxicity Databasementioning
confidence: 99%
“…The reduction in brain protein synthesis has also been linked to high amounts of other amino acids. During brain development, hyperphenylalaninemia can diminish myelin production, as seen by decreased incorporation of methionine into myelin proteins [39], decreased total lipid content, decreased myelin yield, [40], and overall lower brain weight [41]. Aspartame and its constituent amino acids have been studied for their impact on baby development.…”
Section: Mechanism Of Action Despite the Food And Drugmentioning
confidence: 99%